2021
DOI: 10.1111/aos.15034
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of nanofibrous membranes for culturing of primary RPE cells compared to commercial scaffolds

Abstract: Purpose: Dysfunction of the retinal pigment epithelium (RPE) causes numerous forms of retinal degeneration. RPE replacement is a modern option to save vision. We aimed to test the results of transplanting cultured RPEs on biocompatible membranes. Methods:We cultivated porcine primary RPE cells isolated from cadaver eyes from the slaughterhouse on two types of membranes: commercial polyester scaffolds Transwell (Corning Inc., Kenneburg, ME, USA) with 0.4 µm pore size and prepared Poly (L-lactide-co-DL-lactide) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…Before performing the experiments, the cultures were carefully rinsed with DPBS and the cells were harvested by incubating the cultures on TrypLE TM (Gibco ® , Thermo Fisher Scientific, Waltham, MA, USA) for 5 min at 37 • C in a 5% CO 2 atmosphere. The cells were then seeded on either commercially available inserts (Corning Transwell polycarbonate (PC) membrane cell culture inserts, 6.5 mm diameter, 0.4 µm pore) or coated or uncoated electrospun polylactide-based (PLA) membranes (PLA membranes characterized elsewhere, cell culture insert wit 10 mm diameter, PLA membrane with 0.4 µm pore size, porosity of 72%, membrane thickness of 3.7 µm, and fiber diameter of 380 nm) [2,10] at a density of 1.5 × 10 5 −1.8 × 10 5 cell/cm 3 . For coating, Matrigel ® was used at a concentration of 8.7 µg/cm 3 , which was deposited on target PLA membranes, cultured for 1 h at 37 • C, and subsequently rinsed with DPBS.…”
Section: Cell Isolation Culture Passage and Seedingmentioning
confidence: 99%
See 3 more Smart Citations
“…Before performing the experiments, the cultures were carefully rinsed with DPBS and the cells were harvested by incubating the cultures on TrypLE TM (Gibco ® , Thermo Fisher Scientific, Waltham, MA, USA) for 5 min at 37 • C in a 5% CO 2 atmosphere. The cells were then seeded on either commercially available inserts (Corning Transwell polycarbonate (PC) membrane cell culture inserts, 6.5 mm diameter, 0.4 µm pore) or coated or uncoated electrospun polylactide-based (PLA) membranes (PLA membranes characterized elsewhere, cell culture insert wit 10 mm diameter, PLA membrane with 0.4 µm pore size, porosity of 72%, membrane thickness of 3.7 µm, and fiber diameter of 380 nm) [2,10] at a density of 1.5 × 10 5 −1.8 × 10 5 cell/cm 3 . For coating, Matrigel ® was used at a concentration of 8.7 µg/cm 3 , which was deposited on target PLA membranes, cultured for 1 h at 37 • C, and subsequently rinsed with DPBS.…”
Section: Cell Isolation Culture Passage and Seedingmentioning
confidence: 99%
“…Several promising transplantation studies have already been performed on rodents and pigs [8,9]. Electrospun PLA-based membranes have especially exhibited excellent properties in comparison to commercial polyester inserts [10]. In general, one of the most important advantages of ultrathin nanofibrous PLA-based membranes in comparison to commercial membranes is that their thickness corresponds very well to the thickness of healthy Bruch's membrane to which RPE cells adhere in the eye.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrathin nanofibrous scaffolds based on degradable polylactide (PDLLA) facilitated the physiological flow of nutrients through porosity over 70% and thus preserved the functioning of RPE cells. 88 Ultrathin PDLLA nanofibrous membrane with thickness of 3-4 µm corresponds with thickness of Bruch’s membrane of 2-6 µm, however, the wet ultrathin membrane is difficult to handle during biological and surgical manipulations. Popelka et al reported embedding of the peripheral frame into the nanofibrous PDLLA membrane that enabled the ultrathin membrane to be handled without irreversible folding and allowed the membrane to regain its flat shape when transplanted subretinally.…”
Section: Delivery Of Rpe To the Subretinal Spacementioning
confidence: 99%